Common core literacy for ELA, history/social studies, and the humanities : strategies to deepen content knowledge (grades 6-12) - McKnight, Katherine S. 4 0 (Katherine Siewert),16; 5 (San Francisco, CA : Jossey-Bass, a Wiley brand/Staff Development for Educators, 2014)
This book help[s] teachers understand what literacy looks like in English/Language Arts (ELA), Social Studies and other humanities-related subjects (such as: philosophy, psychology, history, classics, drama, for[ei]gn language, and art), and shows them how to develop these literacy skills in their students--Provided by publisher.
Grades 6-12--Front cover.
Includes bibliographical references (pages 187-189) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; Study and teaching (Secondary);Standards.;Standards.;Study and teaching;Standards.;Standards. -- Content area reading;Language arts (Secondary);Reading;Language arts -- United States;United States;United States; 20; 2